2013
DOI: 10.1517/17425255.2013.816285
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking effect on HIV-1 pathogenesis: role of cytochrome P450 isozymes

Abstract: Introduction Tobacco smoking is highly prevalent among the HIV-1-infected population. In addition to diminished immune response, smoking has been shown to increase HIV-1 replication and decrease response to antiretroviral therapy, perhaps through drug–drug interaction. However, the mechanism by which tobacco/nicotine increases HIV-1 replication and mediates drug–drug interaction is poorly understood. Areas covered In this review, the authors discuss the effects of smoking on HIV-1 pathogenesis. Since they pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 94 publications
(102 reference statements)
2
37
0
Order By: Relevance
“…This may lead to an increased risk of cancer in HIV-1-positive smokers compared with HIV-negative smokers. Indeed, our recent study showed an increase in oxidative DNA damage and viral load in the plasma of HIV-1-positive smokers compared to HIV-1-positive non-smokers (data not shown; Ande et al, 2013). We also reported enhanced oxidative stress that was correlated with an increase in the viral load in HIV-1-positive smokers compared with HIV-1-positive nonsmokers (Ande et al, 2013).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This may lead to an increased risk of cancer in HIV-1-positive smokers compared with HIV-negative smokers. Indeed, our recent study showed an increase in oxidative DNA damage and viral load in the plasma of HIV-1-positive smokers compared to HIV-1-positive non-smokers (data not shown; Ande et al, 2013). We also reported enhanced oxidative stress that was correlated with an increase in the viral load in HIV-1-positive smokers compared with HIV-1-positive nonsmokers (Ande et al, 2013).…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, our recent study showed an increase in oxidative DNA damage and viral load in the plasma of HIV-1-positive smokers compared to HIV-1-positive non-smokers (data not shown; Ande et al, 2013). We also reported enhanced oxidative stress that was correlated with an increase in the viral load in HIV-1-positive smokers compared with HIV-1-positive nonsmokers (Ande et al, 2013). Previous reports also suggest a role of smoking in increased viral replication and a possible association with increased oxidative stress (Boelaert et al, 1996;Israel and GougerotPocidalo, 1997;Aquaro et al, 2007).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Such a contention is plausible based on findings that the magnitude of HIV replication is a strong predictor of the rate of progression to AIDS [68] and is supported by several in vitro studies, mentioned earlier, which have shown that smoking enhances HIV-1 replication in alveolar macrophages, microglia and T-cells [58][59][60]. It has been suggested that iron and oxidative stress are possible mechanisms of enhanced production of HIV-1 by alveolar macrophages in cigarette smokers [69,70]. In contrast, a number of clinical studies has failed to confirm accelerated disease progression in smokers [71][72][73][74][75][76][77][78], most probably because they were restricted to specific high-risk groups, such as men who have sex with men and injection-drug users.…”
Section: Effects Of Smoking On Hiv Disease Progression and Treatmentmentioning
confidence: 89%
“…Notwithstanding the counteracting immunosuppressive effect of HIV/smoking on the efficacy of therapy, other possible causes of smoking-related interference with HAART include 1) smoking is a surrogate marker of a noncompliant disposition [81,82]; 2) higher frequencies of side-effects in smokers, including neuropsychiatric symptoms associated with efavirenz-based HAART regimens [83]; 3) negative effects of smoking-related activation of cytochrome P450 enzymes, such as the CPY1A1-m1 variant, which promote oxidative conversion of smoke-derived toxicants to DNA adducts, causing activation of genes that support HIV replication [70,84]; 4) altered pharmacokinetics of antiretroviral agents, possibly related to smoking-mediated induction of CYP3A4 and aryl-hydrocarbon-hydroxylases [85,86], which metabolise many protease and non-nucleoside reverse transcriptase inhibitors [87,88]; and 5) smoking-induced mitochondrial oxidative stress [89], which may exacerbate the adverse effects of antiretroviral drugs that induce mitochondrial toxicity, such as drugs from the nucleoside reverse transcriptase inhibitor class [90].…”
Section: Effects Of Smoking On Hiv Disease Progression and Treatmentmentioning
confidence: 99%